Geospatial Data Visualization with Spatio Temporal Analysis method: The Effect of Hotel Accommodation Distribution on Poverty Level in East Java Province - Nasywa Agra Nisrina; Seftin Fitri Ana Wati; Faradhiya Aulia Rahma; Arista Pratama; Edwin Erifiandi (International Journal of Computer, Network Security and Information System, 2024)
Tourism accommodation distribution influences regional poverty rates, making accurate data essential for analysis. This study aims to create a data visualization on poverty rates and tourism accommodation, especially hotels, in East Java Province to examine the relationship between the two through geospatial data visualization. By using the spatio-temporal analysis method starting from data preprocessing, data integration, data identification, and data visualization, this process allows comprehensive mapping and analysis of the available data. The resulting data visualization will be very useful for stakeholders in identifying and understanding the relationship between the availability of tourism facilities and economic welfare. Through this visual representation, stakeholders can clearly see how the distribution of tourism accommodations, such as hotels, can affect poverty levels in different regions. The statistical analysis using an F-test regression model confirms a significant relationship, with an F-value of 7.19 and a p-value of 0.003, indicating that an increase in hotel accommodations is associated with a decrease in poverty levels. This is due to the potential opening of jobs in the tourism sector for local residents in each district or city area.